Self-learning of point-of-care cardiac ultrasound - Can medical students teach themselves? - Lior Fuchs; David Gilad; Yuval Mizrakli; Re'em Sadeh; Ori Galante; Sergio Kobal (PLoS ONE, 2018)
BACKGROUND:Point-of-care ultrasonography (PoCUS) is a rapidly evolving discipline that aims to train non-cardiologists, non-radiologists clinicians in performing bedside ultrasound to guide clinical decision. Training of PoCUS is challenging, time-consuming and requires large amount of resources. The objective of our study was to evaluate if this training process can be simplified by allowing medical students self-train themselves with a web-based cardiac ultrasound software. METHODS:A prospective, single blinded, cohort study, comparing performance of 29 medical students in performing a six-minutes cardiac ultrasound exam. Students were divided into two groups: self-learning group, using a combination of E-learning software and self-practice using pocket ultrasound device compared to formal, frontal cardiac ultrasound course. RESULTS:All 29 students completed their designated courses and performed the six-minutes exam: 20 students participated in the frontal cardiac ultrasound course and 9 completed the self-learning course. The median (Q1,Q3) test score for the self-learning group was higher than the frontal course group score, 18 (15,19) versus 15 (12,19.5), respectively. Nevertheless, no statistically significant difference was found between the two study groups (p = 0.478). All students in the self-learning course group (9/9, 100%) and 16 (16/20, 80%) of students in the frontal ultrasound course group obtained correct alignment of the parasternal long axis view (p = 0.280). CONCLUSIONS:Self-learning students combining E-learning software with self-practice cardiac ultrasound were as good as students who received a validated, bedside, frontal cardiac ultrasound course. Our findings suggest that independent cardiac ultrasound learning, combining utilization of E-learning software and self-practice, is feasible. Self-E- learning of cardiac ultrasound may serve as an important, cost-effective adjunct to heavily resource consuming traditional teaching.